In vitro and in ovo impact of the ionic dissolution products of boron-doped bioactive silicate glasses on cell viability, osteogenesis and angiogenesis - Decker, Simon; Arango-Ospina, Marcela; Rehder, Felix; Moghaddam-Alvandi, Arash; Simon, Rolf; Merle, Christian; Renkawitz, Tobias; Boccaccini, Aldo R.; Westhauser, Fabian (Scientific reports, 2022)
Due to the pivotal role of angiogenesis in bone regeneration, the angiogenic properties of biomaterials are of high importance since they directly correlate with the biomaterials’ osteogenic potential via ‘angiogenic-osteogenic coupling’ mechanisms. The impact of bioactive glasses (BGs) on vascularization can be tailored by incorporation of biologically active ions such as boron (B). Based on the ICIE16-BG composition (in mol%: 49.5 SiO2, 36.3 CaO, 6.6 Na2O, 1.1 P2O5, 6.6 K2O), three B-doped BGs have been developed (compositions in mol%: 46.5/45.5/41.5 SiO2, 36.3 CaO, 6.6 Na2O, 1.1 P2O5, 6.6 K2O, 3/4/8 B2O3). The influence of B-doping on the viability, cellular osteogenic differentiation and expression of osteogenic and angiogenic marker genes of bone marrow-derived mesenchymal stromal cells (BMSCs) was analyzed by cultivating BMSCs in presence of the BGs’ ionic dissolution products (IDPs). Furthermore, the influence of the IDPs on angiogenesis was evaluated in ovo using a chorioallantoic membrane (CAM) assay. The influence of B-doped BGs on BMSC viability was dose-dependent, with higher B concentrations showing limited negative effects. B-doping led to a slight stimulation of osteogenesis and angiogenesis in vitro. In contrast to that, B-doping significantly enhanced vascularization in ovo, especially in higher concentrations. Differences between the results of the in vitro and in ovo part of this study might be explained via the different importance of vascularization in both settings. The implementation of new experimental models that cover the ‘angiogenic-osteogenic coupling’ mechanisms is highly relevant, for instance via extending the application of the CAM assay from solely angiogenic to angiogenic and osteogenic purposes.
Gesehen am 22.06.2022